SOSIALISASI SISTEM INTEGRASI SAPI DAN KELAPA SAWIT DI DESA TELUK MERBAU, KECAMATAN DAYUN, KABUPATEN SIAK DAN POTENSINYA SEBAGAI SUMBER PUPUK ORGANIK - Siti Mashitoh, Anjar; Hartati, Nina; Trisna, Meyci; Kurniawan, Edi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The SISKA program, which combines cattle farming in the same area as oil palm, allows an attachment between crops and livestock in utilizing waste. This program can be aligned with the Cattle Grant Program from the Ministry of Agriculture which has been taking place in Teluk Merbau Village, Dayun District, Siak Regency since 2007. This community service was carried out from December 1 to 15, 2024. The stages of the service began with discussions with village officials, visits to the plantation area, implementation of socialization followed by discussion and questions and answers, delivery of material and distributing questionnaires to respondents involved in the activity. Plantation farmers who receive cattle grants are expected to be able to process the cow dung waste produced properly so that it can be used as a source of organic fertilizer to be applied to their oil palm land. The use of organic fertilizers as a companion to chemical fertilizers on oil palm land is expected to increase land productivity and reduce environmental pollution.